Canadian centre for mental health and sport (CCMHS) position statement: Principles of mental health in competitive and high-performance sport - Van Slingerland, K. J.; Durand-Bush, N.; Bradley, L.; Goldfield, G.; Archambault, R.; Smith, D.; Edwards, C.; Delenardo, S.; Taylor, S.; Werthner, P.; Kentta, G. (Clinical Journal of Sport Medicine, 2019)
The brave decision made by many Canadian athletes to share their experience with mental illness has fed a growing dialogue surrounding mental health in competitive and high-performance sport. To affect real change for individuals, sport culture must change to meet demands for psychologically safe, supportive, and accepting sport environments. This position statement addresses mental health in competitive and high-performance sport in Canada, presenting solutions to current challenges and laying a foundation for a unified address of mental health by the Canadian sport community. The paper emerged from the first phase of a multidisciplinary Participatory Action Research (PAR) project, in which a sport-focused mental health care model housed within the Canadian Centre for Mental Health and Sport (CCMHS) is currently being designed, implemented, and evaluated by a team of 20 stakeholders, in collaboration with several community partners and advisors.